Dampak Efisiensi Anggaran Pendidikan terhadap Kualitas Pengajaran Guru Honorer di NTT: Kasus Agustinus SD Negeri Batu Esa Kupang - Allya Arjani Putri; Anindya Naylal Husna; Annisaa Dwi Astrid; Ayu Puspitasari; Grisella Khalisha Putri Ayuningtyas; Khilda Fatmawati; Muhammad Andhika Dwi Perdana; Naila Azaria Arumi; Abdul Ghofur; Hendika Wicaksana (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the impact of education budget efficiency policies on the teaching quality of honorary teachers in East Nusa Tenggara (NTT), focusing on the case of Agustinus, a teacher at SD Negeri Batu Esa, Kupang. The research is motivated by the implementation of fiscal efficiency policies under Presidential Instruction No. 1 of 2025, which potentially affects the welfare of non-civil servant teachers. This study aims to analyze how budget efficiency influences teachers’ income stability, socio-economic vulnerability, and teaching performance. A qualitative descriptive case study approach is employed, utilizing primary data from documentary sources and media interviews, as well as secondary data from official reports and academic literature. The analysis is guided by Human Capital Theory and Distributive Justice Theory to understand the relationship between teacher welfare and educational outcomes. The findings reveal that budget efficiency policies have led to significant income reductions, payment instability, and increased economic vulnerability among honorary teachers. These conditions force teachers to seek additional income sources, reducing their focus and energy for teaching activities. Consequently, the quality of instruction is potentially affected, particularly in disadvantaged regions with limited infrastructure.